Concept of Time in Virginia Woolf’s To the Lighthouse: Bergsonian Study - Fatemeh Sadat Basirizadeh; Shiva Zaheri Birgani; Narges Raoufzadeh; Viona Sapulette (Britain International for Academic Research (BIAR-Publisher), 2021)
Time is an important element in modern literature, has always been one of the most important themes of Virginia Woolf’s novels. The purpose of this paper is to look at Woolf treatment of the movement of time within the conscious mind in the novel in title of To the Light House by Virginia Woolf. One conclusion drawn from this study is that Woolf began to use time as a literary element, thereby decreasing her development of plot and characterization. A second conclusion is that she was greatly influenced by the philosophy of Henri Bergson and that consequently her writing increasingly reflects the fluid movement of time within consciousness. This paper demonstrates that Virginia Woolf used time as a formal element of narrative to show the relationship of time to human consciousness; and she never overlooked the fact that time moves human beings toward death. For Woolf, life is characterized by endless variety and movement. Its exquisite beauty is enhanced by knowing that we humans live short lives and lose everything when we die.